Introduction to Java - Evans, Benjamin J. (O'Reilly Media, 2014)
"This unique video course goes beyond the usual introductory classes for poeple just learning how to program. Instead, Introduction to Java is geared toward people in (or about to enter) the tech industry who want to enhance their careers by learning Java's application."--Resource description page.
Title from resource description page (viewed Oct. 7, 2014)
Keywords: Java (Computer program language); Java (Langage de programmation)